Small bowel obstruction, incisional hernia and survival after laparoscopic and open colonic resection (LAFA study). Issue 9 (30th June 2014) - Bartels, S. A. L.; Vlug, M. S.; Hollmann, M. W.; Dijkgraaf, M. G. W.; Ubbink, D. T.; Cense, H. A.; van Wagensveld, B. A.; Engel, A. F.; Gerhards, M. F.; Bemelman, W. A.; the Collaborative LAFA Study Group; Cuesta, M. A.; et al.
<x xml:space="preserve">Abstract</x> Background Short‐term advantages to laparoscopic surgery are well described. This study compared medium‐ to long‐term outcomes of a randomized clinical trial comparing laparoscopic and open colonic resection for cancer. Methods The case notes of patients included in the LAFA study (perioperative strategy in colonic surgery; LAparoscopy and/or FAst track multimodal management versus standard care) were reviewed 2–5 years after randomization for incisional hernia, adhesional small bowel obstruction (SBO), overall survival, cancer recurrence and quality of life (QoL). The laparoscopic and open groups were compared irrespective of fast‐track or standard perioperative care. Results Data on incisional hernias, SBO, survival and recurrence were available for 399 of 400 patients: 208 laparoscopic and 191 open resections. These outcomes were corrected for duration of follow‐up. Median follow‐up was 3·4 (i.q.r. 2·6–4·4) years. Multivariable regression analysis showed that open resection was a risk factor for incisional hernia (odds ratio (OR) 2·44, 95 per cent confidence interval (c.i.) 1·12 to 5·26; P = 0·022) and SBO (OR 3·70, 1·07 to 12·50; P = 0·039). There were no differences in overall survival (hazard ratio 1·10, 95 per cent c.i. 0·67 to 1·80; P = 0·730) or in cumulative incidence of recurrence (P = 0·514) between the laparoscopic and open groups. There were no measured differences in QoL in 281 respondents (P > 0·350 for all scales). Conclusion Laparoscopic colonic surgery led to fewer incisional hernia and adhesional SBO events. Registration number: NTR222 (http://www.trialregister.nl).